Power quality analysis based on root mean square and discrete fourier transform / Noor Asilah Yaacob - Noor Asilah, Yaacob (2018)
Power Quality (PQ) disturbance is the most significant power issues concern by the customer side due to degradation of the power quality. The root cause of PQ disturbance can be identified by analyzing the characteristics of disturbances. From that, appropriate action can be conducted. The PQ disturbances in the voltage waveform are very difficult to identify using normal human sight. It is also difficult to analyze the PQ disturbance manually because of dealing with the huge sample of data waveform. Besides, the method in sag magnitude determination should be improved to get more relevant result. This project presents two methods for analyzing the PQ disturbance based on Root Mean Square (RMS) and Discrete Fourier Transform (DFT). A new technique is introduced to determine the voltage sag magnitude. This method is applied to the voltage waveform data as provided by the IEEE 1159.2 PQ event working group using MATLAB programming. The proposed method for sag magnitude determination is added by modifying the program of RMS and DFT measurement using Rectangular Approximation technique. For the result, the RMS and DFT method can use to analyze the voltage sag event. Both methods able to analyze the voltage sag detection time, sag duration and sag magnitude. The comparison performance between RMS and DFT method in voltage sag analysis is presented. The analysis result is affected by the sliding window technique and the size of the rectangle in the sag magnitude determination. For future work in this project, the method can be modified to analyze other types of PQ disturbances like swell, transient and harmonics for more practical.